Circle of death [compact disc, unabridged] - Patterson, James, 1947-; Sitts, Brian (The Shadow Thriller, 2023)
In 2088, the World Destroyer is on the loose. Not even Lamont Cranston, The Shadow's alter ego, knows who he is. But as people drop dead, it's up to The Shadow to stop the end of the world.